A rare cause of acute ST-elevation myocardial infarction: case report of native aortic valve thrombosis. Issue 1 (31st December 2019) - Beekman-van Solkema, Gerrie; Schoots, M H; Pundziute-Do Prado, G
Abstract: Background: One to 13% of all patients with the clinical diagnosis of an acute coronary syndrome (ACS) show no evidence of significant obstructive coronary artery disease on angiography. Less common causes should be considered in those situations. A very rare cause of ACS is native aortic valve thrombosis. Case summary: A 69-year-old previously healthy woman presented with acute chest pain. The electrocardiogram showed an anterolateral ST-elevation myocardial infarction (STEMI). She was immediately transferred for primary percutaneous coronary intervention. Shortly after arriving in hospital her condition deteriorated, with development of cardiogenic shock necessitating cardiopulmonary resuscitation. A coronary angiogram was performed during resuscitation that did not reveal any obstructive coronary artery disease. Echocardiography showed no pericardial effusion, no significant left-sided valve pathology, no signs of an aortic dissection or pulmonary embolism. She died of cardiogenic shock of unknown cause. Permission for autopsy was obtained. Pathologic examination revealed a large anterolateral myocardial infarction caused by a mass attached to the bottom of the left coronary cusp of the native aortic valve, which was large enough to occlude the ostium of the left main coronary artery. Microscopic analysis showed a thrombus of unknown origin. The aortic valve itself showed no signs of pathology. Discussion: An ST-elevation myocardial infarction due to native aortic valve thrombosis is a rare condition, especially when there are no significant valvular abnormalities. This case demonstrates that thrombosis can develop in an apparently healthy middle-aged woman without any history of thrombotic disease.